“La justicia indígena y su incidencia en los derechos humanos”. - Gómez Calvopiña, Juan Diego (2023)
The present investigative work will address the problem of competences, parameters and limitations that the application of Indigenous Justice has, within the indigenous communities, peoples and nationalities of Ecuador, with the essential objective of establishing what its incidence has been on Human Rights, which as a result of the lack of legislation, added to the incipient insecurity that the country is going through, has distorted the historical and anthropological nature of indigenous justice.